Cover Image. Issue 4 (30th July 2018) - Kanchanatawan, Buranee; Sriswasdi, Sira; Thika, Supaksorn; Stoyanov, Drozdstoy; Sirivichayakul, Sunee; Carvalho, André F.; Geffard, Michel; Maes, Michael
Abstract : The cover image, by Buranee Kanchanatawan M.D et al., is based on the Original Article Towards a new classification of stable phase schizophrenia into major and simple neuro‐cognitive psychosis: Results of unsupervised machine learning analysis, DOI:https://doi.org/10.1111/jep.12945 .